2012
DOI: 10.1007/s12010-012-9902-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thermostable Serine Alkaline Protease from an Alkaliphilic Strain Bacillus pumilus MCAS8 and Its Applications

Abstract: This study describes the characterization and optimization of medium components for an extracellular detergent, surfactant, organic solvent and thermostable serine alkaline protease produced by alkaliphilic Bacillus pumilus MCAS8 strain isolated from Pulicat lake sediments, Tamil Nadu, India. The strain yielded maximum protease (2,214 U/ml) under optimized conditions: carbon source, citric acid-1.5 % (w/w); inducer, soyabean meal-2 % (w/w); pH 11.0; shaking condition 37 °C for 48 h. The enzyme had pH and tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 46 publications
7
56
0
Order By: Relevance
“…The highest levels of protease production was achieved in the culture grown at pH 11, thereby indicating the isolate can be classified as alkaliphilic microorganism (data shown in Figure 1). This result is in good agreement with the studies by some researchers, who reported maximum protease activity at pH 11 with B. pumilus [25][26][27] . Similarly, Tekin et al 28 also reported that B. cohnii produced maximum protease at pH 11.…”
Section: Determination Of Optimum Growth Conditionssupporting
confidence: 93%
“…The highest levels of protease production was achieved in the culture grown at pH 11, thereby indicating the isolate can be classified as alkaliphilic microorganism (data shown in Figure 1). This result is in good agreement with the studies by some researchers, who reported maximum protease activity at pH 11 with B. pumilus [25][26][27] . Similarly, Tekin et al 28 also reported that B. cohnii produced maximum protease at pH 11.…”
Section: Determination Of Optimum Growth Conditionssupporting
confidence: 93%
“…All the experiments and assays were performed in triplicate; and the standard deviation for each experiment was calculated using SPSS 14.0 and are indicated in the figures as error bars (JAYAKUMAR et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…B001 where maximal protease production was detected at the mid stationary phase (PATEL et al, 2005;RAJA;PRABHAHAR, 2012). However, protease section by Bacillus pumilus MCAS8 was found to be at late stationary phase (48 h) (JAYAKUMAR et al, 2012). …”
Section: Effect Of Incubation Temperature Media Ph and Aeration Levelmentioning
confidence: 99%
See 2 more Smart Citations